Bilirubin and postpartum depression: an observational and Mendelian randomization study - Liu, Yi; Wang, Zhihao; Li, Duo; Lv, Bin (Frontiers in Psychiatry, 2024)
Background. Postpartum depression (PPD) is one of the most common complications of delivery and usually disregarded. Several risk factors of PPD have been identified, but its pathogenesis has not been completely understood. Serum bilirubin has been found to be a predictor of depression, whose relationship with PPD has not been investigated.Methods. Observational research was performed followed by two-sample mendelian randomization (MR) analysis. From 2017 to 2020, clinical data of pregnant women were retrospectively extracted.Logistic regression and random forest algorithm were employed to assess risk factors of PPD, including serum level of total bilirubin and direct bilirubin. To further explore their potential causality, univariable and multivariable mendelian randomization (MVMR) were conducted.Sensitivity analyses for MR were performed to test the robustness of causal inference.Results. A total of 1,810 patients were included in PPD cohort, in which 631 (34.87%) were diagnosed with PPD. Compared with control group, PPD patient had a significantly lower level of total bilirubin (9.2 umol/L, IQR 7.7, 10.